AN ASSOCIATION BETWEEN COMPONENTS OF THE APOPTOSIS PATHWAY AND THE GENETIC PREDISPOSITION TO ACHILLES TENDINOPATHY. Issue 9 (10th May 2013) - Nell, E; van der Merwe, L; Cook, J; Handley, C J; Collins, M; September, A V
Abstract : Introduction: Achilles tendinopathy is a degenerative condition for which several risk factors have been implicated including components of the inflammatory pathway. The aims of this study was to evaluate (i) several functional variants within genes encoding components of the apoptosis signalling cascade and (ii) the effectiveness of a polygenic apoptosis profile to capture Achilles tendinopathy (TEN) risk. Methods: A total of 358 unaffected control (CON) participants (159 South Africa (SA CON) and 199 Australia (AUS CON)) and 166 affected TEN participants (87 SA TEN and 79 AUS TEN) were genotyped for four variants ( CASP8 (rs384129), CASP8 (rs1045485), NOS3 (rs1799983) and NOS2 (rs2779249)). Logistic regression was used to derive risk models for TEN and a receiver operator characteristic (ROC) curve was plotted to determine the effectiveness of the models to capture TEN risk. Results: An independent association of CASP8 _rs1045485 and CASP8 _rs3834129, together with their haplotype was observed with TEN risk. The optimal risk model identified from the study included the two CASP8 genetic loci investigated ( CASP8 _rs384129 and CASP8 _rs1045485) together with sex to capture TEN risk in both SA and AUS participants collectively. Conclusions: These findings further implicate the apoptosis signalling cascade as one of the important biological pathways involved in the development of Achilles tendinopathy.